PROSES PENCIPTAAN DAN BENTUK TARI BETEMAS DALAM KARYA PERTUNJUKAN TEMAS RITO : SYMPHONY OF HEALING AND SPIRITUALITY - Nailla Salsyabhila Adini; Soemaryatmi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study examines the creation process and performance form of Betemas Dance in the work Temas Rito: Symphony of Healing and Spirituality, which is inspired by the traditional Temas Kunyit healing ritual practiced in Baru Village, Muarajambi. The research aims to analyze the transformation of the healing ritual into a choreographic concept and to explain the arrangement of dance elements that shape the performance structure. This study employed a Practice-Led Research approach with qualitative methods. Data were collected through participant observation, interviews with cultural practitioners and local communities, and literature review, then analyzed through the artistic creation process. The findings reveal that Betemas Dance is an artistic reinterpretation of a traditional healing ritual expressed through representative movements, choreographic structures, and integrated performance elements. The dance represents physical and spiritual healing while highlighting values of togetherness, unity, and local wisdom. The study contributes to the development of research-based dance creation and supports the preservation of traditional cultural practices within contemporary performing arts.